(3cTa GdcQHI aj QaY GdWdHIs - (3eMeO GdHQdSj GdQaGYj GdTGaYjs
(3ChdgG (B:s
(3GdMeO ddg GdPi CbGe bhGe GdTQjYI GdZQGA HeMeOg hHYO agPG JCdja efja ajeG hbY ai gPG GdYGe , GdPi gh YGe SHYI YTQ hCda ef GdLfO GdCTbjGA GddFGe hGdCghGd GdYXGe s
(3HQSe NRGfI GdSjO CMeO Hf eMeO GdHcQi GdUOjbis
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B121 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs